Examination of rheological behavior of MWCNTs/ZnO-SAE40 hybrid nano-lubricants under various temperatures and solid volume fractions - Hemmat Esfe, Mohammad; Afrand, Masoud; Rostamian, Seyed Hadi; Toghraie, Davood (Experimental thermal and fluid science, 2017)
•An examination of viscosity of MWCNT/ZnO-SAE40 hybrid nano-lubricants has been done.•Experiments have been done under various temperatures and solid volume fractions.•The results revealed that the nano-lubricant behaves as Newtonian fluid.•The maximum enhancement of viscosity of the nano-lubricant was 33.3%.•A new correlation has been proposed to estimate the viscosity of MWCNT/ZnO-SAE40 hybrid nanofluid. Engine oil is a type of lubricants and coolants that is used in internal combustion engines. In this paper, an examination of viscosity of MWCNTs/ZnO-SAE40 hybrid nano-lubricants under various temperatures and solid volume fractions is presented. The experiments performed at temperature ranging from 25°C to 60°C and solid volume fractions of 0, 0.05%, 0.075%, 0.1%, 0.2%, 0.4%, 0.5%, 0.75% and 1%. The results revealed that the nano-lubricant behaves as Newtonian fluid. Viscosity measurements also showed that the viscosity decreases with increasing temperature and increases with an enhancement in the solid volume fraction. Using experimental data, relative viscosity indicated that the maximum enhancement of viscosity of the nano-lubricant was 33.3%. This occurred at solid volume fraction of 1.0% and temperature of 40°C. Based on experimental results, the correlation has been proposed to estimate the viscosity of MWCNTs/ZnO-SAE40 hybrid nano-lubricants.